Auricular acupuncture for persistent insomnia and anxiety associated with COVID-19: a case report - Hu, Hantong; Cheng, YingYing; Fang, Lianqiang; Yang, Liping; Li, Xingling (Frontiers in Neurology, 2023)
The coronavirus disease 2019 (COVID-19) has been associated with various psychological symptoms. We report a case of a female patient who was diagnosed with persistent insomnia and anxiety associated with COVID-19, which was successfully treated with nine treatment sessions of auricular acupuncture. This case report provides preliminary evidence to support further research into auricular acupuncture as a potential therapy for persistent insomnia and anxiety associated with COVID-19.